Application of Liposomes in Cancer Therapy: An Assessment of the Advancement of Technology Through Patent Documents - Nunes, Danielle D.G.; Leal, Ingrid L.; Oliveira, Fabricia O.; da Silva, Tatiara L.R.; de Senna, Valter; Machado, Bruna S. S. (Recent Patents on Nanotechnology, 2021)
Background: Cancer is caused by mutations in oncogenes and loss of tumor suppressor activity. Despite the efforts of the pharmaceutical industry to fight cancer, it is necessary to investigate new methods to enhance the action against this disease. In this scenario, liposome technology has emerged as a drug delivery system for cancer treatment. The objective of this study was to evaluate the use of liposome technology in the treatment of cancer through analysis of patent documents. Methods: We analyzed prospective documents in the Derwent Innovation Index database. Results: A total of 203 patent documents were related to the area of interest, published between 2000 and 2020, and the USA and Japan were shown as countries with the largest number of publications. Moreover, most of these publications came from companies, however, also with the representation of important universities, mainly the University of California. According to the International Patent Classification, the codes most applicable to the documents were in the areas of human necessities and chemistry. Conclusion: The results of this study showed that the study and application of liposomes for the development of cancer treatment tended to grow, along with the number of related patents.
Keywords: Cancer